SiO2-GeO2 soot preform as a core for Eu2O3 nanocoating: Synthesis and photophysical study - Rosa, Ieda L. V.; Oliveira, Larissa H.; Suzuki, Carlos K.; Varela, José Arana [UNESP]; Leite, Edson R.; Longo, Elson [UNESP] (Springer/plenum Publishers, 2008)
Nowadays solid state chemists have the possibility of work with low temperature strategies to obtain solid state materials with appropriate physical and chemical properties for useful technological applications. Photonic core shell materials having a core and shell domains composed by a variety of compounds have been synthesized by different methods. In this work we used silica-germania soot prepared by vapor-phase axial deposition as a core where a nanoshell of Eu2O3 was deposited. A new sol-gel like method was used to obtain the Eu2O3 nanoshell coating the SiO2-GeO2 particles, which was prepared by the polymeric precursor method. The photophysical properties of Eu3+ were used to obtain information about the rare earth surrounding in the SiO2-GeO2@Eu2O3 material during the sintering process. The sintering process was followed by the luminescence spectra of Eu3+ and all the samples present the characteristic emission related to the D-5(0) -> F-7(J) (J=0, 1, 2, 3 and 4). The ratios of the D-5(0) -> F-7(2)/D-5(0) -> F-7(1) emission intensity for the SiO2-GeO2@Eu2O3 systems were calculated and it was observed an increase in its values, indicating a low symmetry around the Eu3+ as the temperature increases.
Keywords: europium; luminescence; SiO2-GeO2; core shell; nanocoating